Effect of Stimulus Pattern and Inter-Axis Transfer of Head Rotation in Recalibration of Visual Stability Mechanism - Takase, Masanori; Okajima, Katsunori; Takahara, Kunimitsu (Eizō Jōhō Media Gakkaishi, 2005)
We examined adaptability of a mechanism for stabilizing vision in a conflicting environment, where visual information and head motion were not coherent. We defined “Gain” as the angle ratio of amplitudes of visual motion to those of head motion. First, the subjects adapted to a virtual environment in which they were surrounded by either a sphere or a cube stimulus. The Gain was set at either 0.5 or 1.0 with the head motion following a moving sound for 2 minutes. After this adaptation phase, the subjects adjusted the Gain to obtain the best visual stability. The results showed that the visual stability mechanism starts to recalibrate to such incoherent environments quickly, regardless of the stimulus pattern. Moreover, the results suggested that the visual stability mechanism des not independently process along the yaw and the pitch axes.